Myocardial infarction: risk factors and preventive measures in nuclear industry workers - Yu. V. Semenova; R. M. Takhauov; A. B. Karpov; T. M. Litvinenko; D. E. Kalinkin (Кардиоваскулярная терапия и профилактика)
Aim. To assess the associations between radiation exposure and the risk of acute myocardial infarction (AMI) in nuclear industry workers; to identify the risk factors (RFs) of MI; to suggest relevant preventive measures in this organised population. Material and methods. This ongoing prospective population-based study started in 1998. Over 2001-2006, AMI was diagnosed in 1665 patients, including 439 cases with previous radiation exposure. The case-control analysis included randomly selected AMI cases in 380 workers of the Siberian Chemical Complex (263 and 117 people involved in the main and auxiliary production processes, respectively) and in-hospital controls. For every participant, 65 parameters were registered, including socioeconomic characteristics, RFs, co-morbidities, biochemical parameters (such as total cholesterol), main clinical data, and the total radiation dose.Results. In nuclear industry workers with traditional RFs of AMI, the important risk determinant was not the total radiation dose, but the individual features of radiation dose accumulation. Conclusion. To improve the effectiveness of AMI morbidity and mortality prevention in this organised population, the risk groups should be defined on the basis of the most important RFs. For nuclear industry workers, these RFs include not only traditional risk predictors (arterial hypertension, smoking, hypercholesterolemia, diabetes mellitus), but also the individual features of radiation dose accumulation (age of initial radiation exposure, exposure duration).